Medical Students’ Attitudes toward Abortion Education: Malaysian Perspective - Tey, Nai-Peng; Yew, Siew-Yong; Low, Wah-Yun; Lela, Su’ut; Prachi, Renjhen; Huang, M.S.L.; Tong, Wen-Ting; Lai, Siow-Li (Plos One Publishing, 2012)
Abortion is a serious public health issue, and it poses high risks to the health and life of women. Yet safe abortion services are not readily available because few doctors are trained to provide such services. Many doctors are unaware of laws pertaining to abortion. This article reports survey findings on Malaysian medical students’ attitudes toward abortion education and presents a case for including abortion education in medical schools.